Nail Features of Term Healthy Neonates: An Observational Study - BG Ramya; Manjunath Durgappa; Shwetha Sawant; Kruthika M Reddy; Kallappa C Herakal (Journal of Clinical and Diagnostic Research)
Introduction: Nail disorders in neonates can be indicators of underlying dermatological or systemic disorders, such as Iso-Kikuchi syndrome, Y-shaped bifurcation of the distal phalanx and Nail Patella syndrome. However, there are very few studies describing the features of nails in newborns, especially in the Indian subcontinent. Aim: To study the morphological features of nails in term newborns. Materials and Methods: A descriptive observational study was conducted from November 2021 to July 2022 on term newborn babies born at and visiting Navodaya Medical College Hospital in Raichur, Karnataka, India. A total of 112 babies born to mothers without any co-morbidities were included in the study. Birth and antenatal history were recorded. Finger and toenails were systematically examined, photographed and data were collected regarding fingernail shape, toenail length, width, width ratio and pigmentation. Results: A total of 112 newborns were studied, of which 58 were males and 54 were females, with a mean age of 3±1.5 days. The mean fingernail length, width and width ratio were 4.70±0.53 mm, 3.41±0.11 mm and 0.55±1.95, respectively. Macronychia was observed in 39 newborns (34.8%). The most common fingernail shape was rectangular, observed in 91 (81.25%) cases. The lunula was present in 54 neonates (48.2%). The mean toenail length, width and width ratio were 2.7±0.17 mm, 3.23±0.73 mm and 0.56±1.78, respectively. Micronychia was noted in 65 neonates (58.0%) and macronychia in 8 (7.1%). Hyperpigmentation of the distal phalanx was noted in nine dark-skinned neonates, while 23 newborns (20.5%) exhibited pseudo-hypertrophy of fingernails and 38 newborns (33.9%) showed pseudo-hypertrophy of toenails. Conclusion: Macronychia is common in the fingernails of newborns, whereas micronychia is more common in toenails. Koilonychia can be a physiological finding at birth and the lunula is less common in toes compared to fingernails in newborns.